2021
DOI: 10.1177/20587384211042124
|View full text |Cite
|
Sign up to set email alerts
|

Steroids plus antiviral agents are more effective than steroids alone in the treatment of severe Bell’s palsy patients over 40 years of age

Abstract: Objective The effectiveness of the combination of steroids and antiviral agents in the treatment of Bell’s palsy remains unclear. This study evaluated the therapeutic effect of combination therapy in severe Bell’s palsy patients and assesses specific conditions under which combination therapy is more effective than steroids alone. Methods From January 2005 to December 2019, the records of 1710 Bell’s palsy patients who visited Kyung Hee University Hospital were reviewed retrospectively. Of these, 335 (19.6%) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
10
0
5
Order By: Relevance
“…Kim et al performed a retrospective study on 1710 Bell's palsy patients, comparing the effectiveness of steroids plus antiviral agents vs. steroids alone in treating severe Bell's palsy patients over 40 years old. Subgroup analysis showed the combination therapy resulted in significantly higher recovery rates than steroids alone (77.5% vs. 64.1%, p=0.023) [14]. A randomized controlled trial by Shahidullah et al found similar results, preferring antiviral and steroid combination therapy for improved recovery after Bell's palsy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al performed a retrospective study on 1710 Bell's palsy patients, comparing the effectiveness of steroids plus antiviral agents vs. steroids alone in treating severe Bell's palsy patients over 40 years old. Subgroup analysis showed the combination therapy resulted in significantly higher recovery rates than steroids alone (77.5% vs. 64.1%, p=0.023) [14]. A randomized controlled trial by Shahidullah et al found similar results, preferring antiviral and steroid combination therapy for improved recovery after Bell's palsy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been done to determine the best treatment approach for Bell's palsy, and the consensus is that antivirals in addition to steroids are more effective than steroids alone. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy with steroids and antiviral agents resulted in significantly higher favorable recovery rates than steroids alone in severe Bell's palsy patients. Combination therapy was particularly more effective than steroids alone in patients aged ≥40 years and in patients without hypertension and diabetes (57,58).…”
Section: Antiviral Therapy and Combined Antiviral-steroid Treatmentmentioning
confidence: 94%
“…In a cross sectional convenience study conducted by Mani and Ibrahim, intensive care unit (ICU) nursing staff role were studied and a wide gap existed between concept of the role and method of the caring process at the end of life among professional caring staff and family members of patients (57). This gap needs to be addressed by education accompanied by a formulation of end-of-life care policy in ICUs which is in agreement with culture and belief among the Saudi population.…”
Section: Deathmentioning
confidence: 99%